Performance assessment of primary health care facilities in Brazil: Concordance between web-based questionnaire and in-person interviews with health personnel - Nunes, Luceime Olivia; Castanheira, Elen Rose Lodeiro [UNESP]; Sanine, Patricia Rodrigues [UNESP]; Akerman, Marco; Nemes, Maria Ines Baptistella (Public Library of Science (PLoS), 2023)
This study is a concordance analysis comparing answers to two external assessment tools for Primary Health Care (PHC) facilities that use two different data collection methodologies: (a) external assessment through structured interviews and direct observation of facilities conducted by the National Program for Improvement of Access and Quality of Primary Care (AE-PMAQ-AB), and (b) a computerized web-based self-administered questionnaire for Assessment of the Quality of Primary Health Care Services (QualiAB). The two surveys were answered by 1,898 facilities located in 437 municipalities in the state of São Paulo, Brazil, between 2017 and 2018. Both surveys aimed to assess the management and organization of PHC facilities. A total of 158 equivalent questions were identified. The answers were grouped by thematic similarity into nine domains: Territory characteristics; Local management and external support; Structure; Health promotion, disease prevention, and therapeutic procedures; Attention to unscheduled patients; Women’s health; Children’s health; Attention to chronic conditions; and Oral health. The results show a high level of concordance between the answers, with 81% of the 158 compared questions showing concordance higher than 0.700. We showed that the information obtained by the web-based survey QualiAB was comparable to that of the structured interview-based AE-PMAQ-AB, which is considered the gold standard. This is important because web-based surveys are more practical and convenient, and do not require trained interviewers. Online assessment surveys can allow immediate access to answers, reports and guidelines for each evaluated facility, as provided by the QualiAB system. In this way, the answers to this type of survey can be directly employed by users, allowing the assessment to fulfill all phases of an assessment process.